The anatomy of terror : - Introd. by Nathaniel Weyl. (Public Affairs Press, 1956)
Authorized facsimile produced in 1975 by Xerox University Microfilms, Ann Arbor, Mich. "Thumbnail sketches of persons mentioned in Khrushchev's speech": p. 17-18, reprinted from the New York Times, June 5, 1956.